Significance of tri-hybrid nanoparticles in thermal management subject to magnetized squeezing flow of a Boger-micropolar nanofluid between concentring disks - Ali, Bagh; Sharif, Humaira; Habib, Danial; Ghazwani, Hassan Ali; Saman, Iqra; Yang, Huizhu (Journal of molecular liquids, 2024)
This study examines the transport phenomenon in which host fluid completely mixed with three different nanoparticles types (ternary hybrid nanofluid) has attract scientist's attention for considering of its significance. The primary reason for the rising interest in tri-hybrid nanofluid is its unique ability to improve thermal performance, which is really useful in various heat exchangers. In the present analysis, the main objective of this article is to examining the laminar, time-dependent, incompressible and two dimensional (2D) trihybrid magnetized squeezing flow of a Boger-micropolar nanofluid between non-porous and porous disk to observe the thermal performance of fluid. This model describes the way to attain a more appropriate heat conductor as compared to bi-hybrid, mono nanofluid. The ternary nanofluid is formulated by adding three types of nano size particles with distinct chemical and physical bonds into water as a base liquid. This mixture helps in purification of environment, decomposing destructive substance and other devices that required cooling. At z=−H(1−at)1/2 the lower disk is fixed and the liquid is squeezing due to movement of top disk with axial direction. At the lower surface a homogeneous suction/injection is imposed. Energy and velocity slip impacts are also considered at the fixed bottom disk. Appropriate similarity functions are imposed to transform the governs equations into non-linear ordinary differential equations (ODE's) and then numerically solved by bvp4c technique in MATLAB environment. The outcomes are then displayed in graphically to investigate the microrotation, velocity and temperature profiles. The temperature profile decreased against tri-hybrid case in the lower disk case and then are enhanced near to the top disk in tri-hybrid case, so finally, we conclude that ternary nano size particles have an excellent thermal conductivity as compared to single and hybrid nanoparticles. The present results are found to be good agreement with existence literature for limited cases. •Significance of tri-hybrid nanoparticles in thermal management is modeled.•Tiwari and Das model for nanoparticles is taken into account for modeling.•Ternary hybrid nanofluid have an excellent thermal conductivity.•Higher inputs of magnetic field cause to twisting behavior between disk.